Entrenamiento proactivo para la mejora de la calidad en el control del proceso por atributos (Proactive training for improving quality in the control pf process by attributes) - Cruz Álvarez, Jesús Gerardo (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. Quality is a complex formula which must be the objective to attain in all companies. Quality includes distinct aspects in the organizations such as metrics, objectives, culture, systems continuous improvement, quality control and the necessary trainings in these aspects. Organizations invest resources such as economics, human, and time in training their personnel aiming to control the problems associated with the quality, this is so especially in those organizations with manual oriented processes rather than automated ones. In these cases the quality system sould be sufficiently robust so the process control would be based upon decisions of the line personnel. This article describes a known technique namely R&R that could be applied and used in those organizations in which the control of processes is bases on the criteria of the operative personnel with the objective to reduce the variation in the processes of decision making thereby improving the process control.